Artistic Appreciation of the Saggar Technique in the Works of Ceramist (Mariwan Jalal( - Mohammed Abdulwahed, Gazang ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This research is an attempt to reveal the artistic appreciation aspect of the Saggar technique in terms of conceptual perception in artistic work, regarding what the artist Mariwan Jalal has explored through the Saggar technique using various methods, which led to the emergence of multiple results that differ from one another. The research addressed the general framework, which consists of the research problem, which poses the following question: What is the artistic appreciation of the Saggar technique in the works of artist Mariwan Jalal? The research significance, research objective, research limitations, and definition of terms. While the theoretical framework addressed two sections: the first: artistic appreciation, and the second: the Saggar technique, then the research procedures were discussed, which consist of the research population, research sample, research methodology, and sample analysis. Then the results and conclusions, recommendations and suggestions, followed by a list of sources and references. DOI: https://doi.org/10.54633/2333-024-057-011